2009
DOI: 10.2460/ajvr.70.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Escherichia coli and Salmonella enterica organisms with reduced susceptibility to ceftriaxone from fecal samples of cows in dairy herds

Abstract: No evidence was found that the use of ceftiofur on dairy farms increases the prevalence or dissemination of Salmonella spp or E coli with reduced susceptibility to ceftriaxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…We did not detect any association between farm-level antibiotic use (including ceftiofur) and farm-level CTX-M E. coli prevalence, a finding that is consistent with previous observations (44,45). A study of 65 dairy farms in the United Kingdom found a significant association between the use of a third-or fourth-generation cephalosporin in the previous 12 months and the presence of CTX-M E. coli on the farm (46).…”
Section: Fig 2 Prevalence Of Samples That Yielded E Coli Isolates Posupporting
confidence: 79%
“…We did not detect any association between farm-level antibiotic use (including ceftiofur) and farm-level CTX-M E. coli prevalence, a finding that is consistent with previous observations (44,45). A study of 65 dairy farms in the United Kingdom found a significant association between the use of a third-or fourth-generation cephalosporin in the previous 12 months and the presence of CTX-M E. coli on the farm (46).…”
Section: Fig 2 Prevalence Of Samples That Yielded E Coli Isolates Posupporting
confidence: 79%
“…Our bedding exposure study clearly illustrates that transmission is feasible, and others have also reported transmission of bacteria through simple contact with the floor, hide, food and water [29], [30], [31]. Consequently, the dramatic expansion of cef R enteric bacteria in food animal populations could be explained in part through a process of environmental selection and transmission back to food animals; the effect shown here is much more dramatic than has been reported for in vivo selection following parenteral administration of ceftiofur [8], [10], [13], [14], [17]. While we designed these experiments to reflect physiologically relevant metabolites and concentrations, our bioassay only measured the biological effect of CFM, but not the actual concentration of CFM.…”
Section: Discussionsupporting
confidence: 59%
“…In the U.S. resistance to 3 rd -generation cephalosporins is most often mediated by a bla CMY-2 gene that is harbored by IncA/C plasmids in enteric bacteria [2], [3]. The prevalence of bla CMY-2 plasmid-bearing Salmonella and Escherichia coli has increased rapidly in the U.S. cattle population over the last decade [4], [5], [6], [7], [8], [9]. For instance, Daniels et al [10] found that at least 97% of dairy herds in Washington State were positive for bla CMY-2 plasmid-bearing E. coli and the U.S. Department of Agriculture [11] reported that the percentage of Salmonella sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceftiofur poses an interesting conundrum because while resistance is prevalent in E. coli and Salmonella in the U.S. (Winokur et al, 2000; Donaldson et al, 2006; Daniels et al, 2007, 2009; Sawant et al, 2007; Heider et al, 2009; Lindsey et al, 2009), empirical studies show either no treatment effect (Singer et al, 2008; Daniels et al, 2009; Mann et al, 2011) or transient and relatively short-term amplification of resistant populations (Jiang et al, 2006; Lowrance et al, 2007) after administration of ceftiofur. Lowrance et al (2007) provided the most convincing evidence that selection occurs in the gastrointestinal tract where there was a proportional increase in the number of ceftiofur-resistant E. coli following 1, 2, or 3 days administration of a ceftiofur crystalline-free acid product.…”
Section: Environmental Fate Of Antibioticsmentioning
confidence: 99%